Which athletes are more vulnerable to mental health symptoms during the COVID-19 crisis? A cross-sectional study - Lima, Y.; Denerel, N.; Devran, S.; Rice, S.; Bayraktar, B. (Research in Sports Medicine, 2024)
The present study evaluated the mental health (MH) of athletes according to a range of variables, including SARS-CoV-2 infection status and sport-specific factors. An online survey was sent to 1636 Turkish professional athletes incorporating standardized scales assessing athlete-specific stress, depression, and anxiety. A total of 579 professional athletes (29% SARS-CoV-2 positive) participated in the study. While female athletes reported higher anxiety scores than males (p < 0.01), the depression scores of the athletes who had been infected with SARS-CoV-2 were significantly higher than athletes who were not infected (p = 0.03). Higher athlete-specific stress, depression, and anxiety scores were associated with participating in an individual sport, experiencing chronic pain, severe sports injury history, and performance concerns (all p < 0.01). MH symptoms in athletes were associated with being infected with SARS-CoV-2, female gender, participating in an individual sport, and performance concerns. MH assessments should be undertaken with athletes to detect vulnerabilities and enable appropriate and timely MH interventions.